The Play of Philosophy: Thinking with Drew Hyland - Barry, Lydia W.; Ewegen, S. Montgomery (Studies in Contemporary Phenomenology, 2026)
This volume on the work of Drew Hyland invites readers to join in the open and responsive dialogue that characterizes philosophical life, according to Hyland. Contributors engage figures from Plato to Heidegger and explore themes including love, beauty, play, and transcendence. Each essay reflects philosophy as a lived, communal practice rather than a doctrinal system. Highlights include a meditation on seduction in Plato's Symposium , an imagined dialogue between Hyland and Hans-Georg Gadamer, and a previously unpublished essay by Hyland on Antonioni's Blowup . This collection honors Hyland's legacy and carries it forward-inviting readers to think, question, and philosophize together with him.